A Case of Drug-Induced Liver Injury Secondary to Natalizumab. (16th June 2020) - Santoiemma, Phillip P.; Maddur, Haripriya; Moore, Christopher M.
Abstract : A 33-year-old Caucasian female with relapsing-remitting multiple sclerosis presented with abdominal pain, nausea, and vomiting and was found to have acute liver injury. After thorough investigation, she was diagnosed with drug-induced liver injury (DILI) thought secondary to redosing of Natalizumab therapy.